Pengembangan Kapasitas Institusi Perbankan Syariah Dalam Penyediaan Infrastruktur Jaringan, SDM dan Produk - Bambang Agus Sumantri (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam, 2014)
Writing in the journal aims to analyze the development of institutional capacity, Islamic banking, network infrastructure, human resources and products of Islamic banking in Indonesia from 2003 to 2013. Where characteristics of a research library journal writing.